An insightful overview of the distribution pattern of polycyclic aromatic hydrocarbon in the marine sediments of the Red Sea - Ghandourah Mohammed A. (Open Chemistry, 2022)
Polycyclic aromatic hydrocarbons (PAHs) are produced during the combustion of coal and oil, and they can cause sediment contamination. Marine sediments are an important source of information regarding human activities in coastal regions and the long-term fate of xenobiotics. PAHs are a serious environmental problem for marine ecosystems because of their detrimental health impacts on species, including endocrine-disrupting activities. The type of organic contaminants in marine sediments is determined by their origin, with PAHs classed as either petrogenic or pyrogenic. Accidental or deliberate discharges and spills of oil from ships, particularly tankers, offshore platforms, and pipelines, especially in the Kingdom of Saudi Arabia, are the most obvious and visible sources of oil pollution in the marine environment. The current review study will be extremely important and beneficial as a desk review as a result of the growing human population and rapid development in the area. The distribution pattern of PAHs along the Red Sea coastal sediments was limited. The majority of research along Saudi Arabia’s Red Sea coast demonstrates pyrogenic and petrogenic origins of PAHs, as well as in other parts of the world. Industrial activity, municipal waste runoff, petroleum spills, and sewage runoff have a significant impact on PAH distribution throughout the Red Sea’s coastal estuaries. However, after the Gulf war in 1992, much of the attention was occurred especially in the Arabian Gulf coast of Saudi Arabia. This study portrayed a comparison of distribution pattern of PAHs with the other parts of the world as well.